One-Stage Repair of Aortic Arch Hypoplasia Associated With Ventricular Septal Defect - Truba, Y.; Sekelyk, R.; Dzyurii, I.; Prokopovych, L.; Golovenko, O.; Lazoryshynets, V. (Ukrainian Journal of Cardiovascular Surgery, 2020)
Background. Aortic arch hypoplasia is a congenital anomaly of the development of the aortic arch characterized by ground. Aortic arch hypoplasia is a congenital anomaly of the development of the aortic arch characterized by hemodynamically significant narrowing of one or more segments of the aortic arch. Aortic arch hypoplasia combined ynamically significant narrowing of one or more segments of the aortic arch. Aortic arch hypop with ventricular septal defect (VSD) characterizes a special category of children who are in serious condition and need ptal defect (VSD) characterizes a special category immediate surgery. Despite the improvement in the results of surgical treatment of this abnormality in recent years, the gery. Despite the imp issue of choosing treatment tactics remains debatable. g The aim. To analyze immediate and long-term results of one-stage aortic arch hypoplasia repair and VSD repair in infants. Materials and methods. From 2011 to 2019, 55 infants underwent simultaneous aortic arch hypoplasia repair in ypoplasia rep conjunction with VSD repair at the National Amosov Institute of Cardiovascular Surgery of the NAMS of Ukraine and junction with VSD repair at the National Amosov Institute of Cardiovascular Surgery Ukrainian Children’s Cardiac Center. There were 30 (55%) male patients and 25 (45%) female patients. The mean age of (55%) male patients and 25 (45%) female patients. The mean ag the patients was 1.3 ± 1.2 months (from 0.1 to 9.1 months), the average body weight was 3.9 ± 1.3 kg (from 2.4 to 8.7 patients was 1.3 ± 1.2 months (from 0.1 to 9.1 months), the average body weight was 3.9 ± 1.3 kg ( kg). The mean body surface area was 0.27 ± 0.1 m2. Antegrade selective cerebral perfusion was performed in 23 (42%) g). The mean body patients during the aortic arch reconstruction. g Results.The hospital mortality rate was 1.8% (n = 1). The average duration of artificial circulation was 108.5 ± 38.6 minpital mortality rate was 1.8% (n = 1). The averag utes (from 55 to 204 minutes), aortic clamping time was 56.9 ± 36.4 minutes (from 21 to 126 minutes), the time of selec(from 55 to 204 minutes), aortic clamping time was 56.9 ± 36.4 minutes (from 21 to 126 minutes) tive cerebral perfusion was 26.4 ± 11.5 minutes (14 to 49 minutes). In eight patients (14.5%) the sternum was spread perfusion was 26.4 ± 11.5 minutes (14 to 49 minutes). In eight patients (14.5%) the sternum was sp apart in the early postoperative period. Echocardiography before discharge revealed the average pressure gradient at the part in the early postoperative period. Echocardiograp site of plasticity of the aortic arch of 20.5 ± 14.9 mm Hg. plasticity of the aortic arch of 20.5 ± 14.9 mm Hg. The mean long-term follow-up was 2.6 ± 2.1 years (from two months to 8.1 years). There were no fatal cases in the reg-term follow-up was 2.6 ± 2.1 years (from two months to 8.1 years) mote period. In 5 (9.1%) patients aortic arch restenosis occurred in the postoperative period; it was successfully treated period. In 5 (9.1%) patients aortic arch restenosis occurred in the postoperative period; it was successfully endovascularly by balloon dilation in 3 patients, the other 2 of them underwent repeated aortic arch repair. Long-term y by balloon dilation in 3 patients, the other 2 of them underwent repeated aortic arch repair. Long follow-up of other patients showed good results with respect to the pressure gradient at the aortic arch. There were p of other patients showed good results with respect to the pressure g no hemodynamically significant gradient after VSD closure. There were no neurological complications in the long-term follow-up. p Conclusions. One-stage complete repair is an effective and safe treatment for infants which provides good immedige complete repair is an effective and safe treatment for infants which provides g ate and long-term results. This surgical strategy may be an acceptable alternative to two-stage surgical treatment of this g complex pathology.